Language Functions of Bikol Proverbs in Facet of Conformity and Non-Conformity to Social Norms - Sapo, Rocel S.; Camalla, Sheena Mae M.; Culubong, Anne Raffielle M.; Cruz, Michelle A. Dela; Loreno, Milky L.; Mirate, Theodore John; Ocampo, Darrel M. (Journal of English Education Forum (JEEF), 2024)
This research study used Pragmatics to examine the language functions of Bikol Proverbs, explore their connections, and understand their importance in the lives of the participants. Specifically, it sought to 1) identify the proverbial expressions that the respondents were familiar with, 2) determine those proverbial expressions that they conformed to and non-conformed from, 3) determine the speech act present in the proverbs, and 4) examine the effects of the proverbial expressions on conformity and non-conformity to social norms. Data was collected through semi-structured interviews and triangulated to strengthen the analysis. An audit trail was utilized to ensure the accuracy and reliability of the findings and to eliminate any bias in the interpretation of the data. The results revealed that the participants had a strong affinity for Bikol proverbs, believing that conforming to these proverbial expressions would shape their lifestyle, moral principles, and standard of living. These proverbs have a significant influence in improving the lifestyle, moral principles, and standard of living of Bikolanos and in instilling values in the younger generation. The preservation of Bikol proverbs, particularly this oral tradition, is recommended for the benefit of locals to value their ancestral heritage including cultural identity, values, and traditions.